2016
DOI: 10.1111/nmo.12826
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences are associated with irritable bowel syndrome and gastrointestinal symptom severity

Abstract: BACKGROUND & AIMS Early adverse life events (EALs) are associated with irritable bowel syndrome (IBS). Exposure to EALs as assessed by the Adverse Childhood Experiences (ACE) questionnaire is associated with greater disease prevalence, but ACE has not been studied in gastrointestinal disorders. Study aims were to: 1) Estimate the prevalence of EALs in the IBS patients using the ACE questionnaire; 2) Determine correlations between ACE and Early Trauma Inventory Self Report-Short Form (ETI-SR) scores to confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
78
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 37 publications
16
78
0
7
Order By: Relevance
“…Each of the 27 items is scored as ‘Yes’=1 or ‘No’=0 (score range 0‐27) . The ETI‐SR has previously been used in studies of EALs in IBS …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the 27 items is scored as ‘Yes’=1 or ‘No’=0 (score range 0‐27) . The ETI‐SR has previously been used in studies of EALs in IBS …”
Section: Methodsmentioning
confidence: 99%
“…3 Early adverse life events (EALs) have been found to increase the risk of developing IBS and can be associated with alterations in the central stress response systems, including the hypothalamic-pituitary-adrenal (HPA) axis. [16][17][18] In addition, studies have supported a dysregulated HPA axis in IBS even in the absence of EALs. 19,20 There are some data in the current literature suggesting that resilience can affect the response to stress, and that resilience scores are associated with changes in brain regions involved in stress responsiveness; 9,11-13 however, to our knowledge, this has not been examined in IBS in regards to symptom severity, quality of life, and physiologic markers of stress.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The second pathway identified by Felitti () is that an adult health issue may occur as a result of chronic stress experienced during childhood. Some potential adult health issues that have been linked to ACEs include obesity (Isohookana, Marttunen, Hakko, Riipinen, & Riala, ; Rehkopf et al, ), poor heart health (Klassen, Chirico, O’Leary, Cairney, & Wade, ; Monnat & Chandler, ; Su et al, ), Type 2 diabetes (Huang et al, ; Monnat & Chandler, ), and digestive disorders (Park et al, ).…”
Section: Medical Implications Of Acesmentioning
confidence: 99%
“…Studies have also identified associations between childhood adversity and trauma and specific adult diagnoses including fibromyalgia [35], migraine [36], irritable bowel syndrome [37], insomnia and insufficient sleep [38], cancer [39], cognitive function in mental health disorders [40], as well as learning and behavior problems and obesity in youth [41] and adolescent pregnancy and fetal death [42]. Collectively, this research suggests the significant and pervasive negative impact of childhood ACEs and trauma on short- and long-term health outcomes, and therefore, the necessity and opportunity to prevent and intervene on ACEs, and to provide trauma-informed services broadly to offset the negative consequences in children, the adults they will become, and possibly even future generations.…”
Section: Aces and Traumamentioning
confidence: 99%